Efficacy of transdiagnostic cognitive-behavioral therapy for anxiety and depression in adults, children and adolescents: A meta-analysis - García-Escalera, Julia; Chorot, Paloma; Valiente, Rosa M.; Reales, José M.; Sandín, Bonifacio (Revista de Psicopatología y Psicología Clínica, 2017)
Abstract: This meta-analysis examined the effect of transdiagnostic cognitive-behavioral therapy (T-CBT) in adults, children, and adolescents with emotional disorders, exploring the effects of possible moderator variables on efficacy. In contrast with previous reviews, only studies employing transdiagnostic theory-based protocols were included. A total of 48 studies reporting on 6291 participants were identified. Treatment efficacy was examined using a random effects model and taking into account pre- and post-treatment data. Results within the adult population showed large overall effect sizes on anxiety (randomized controlled trials [RCTs]: g = 0.80; Uncontrolled studies: g = 1.02) and depression (RCTs: g = 0.72; Uncontrolled studies: g = 1.08) that were stable at follow up. Preliminary analysis with children and adolescents showed medium effect sizes on anxiety (g = 0.45) and depression (g = 0.50). No significant differences between T-CBT and disorder-specific CBT were found. Overall, results support the efficacy of T-CBT for emotional disorders. Resumen: Eficacia de la terapia cognitivo conductual transdiagnóstica en el tratamiento de la ansiedad y la depresión en adultos, niños y adolescentes: Un meta-análisis. El presente meta-análisis examina el efecto de la terapia cognitivo conductual transdiagnóstica (TCC-T) en adultos, niños y adolescentes con trastornos emocionales, explorando los efectos de posibles variables moderadoras en su eficacia. A diferencia de los meta-análisis previos, sólo se incluyeron los estudios que emplearon protocolos basados explícitamente en el enfoque transdiagnóstico. Se identificaron 48 estudios que informaron sobre 6291 participantes. La eficacia del tratamiento se examinó utilizando un modelo de efectos aleatorios y teniendo en cuenta los datos pre y post-tratamiento. Los resultados sobre población adulta muestran tamaños del efecto elevados para la ansiedad (ensayos controlados aleatorizados [ECAs]: g = 0.80; Estudios no controlados: g = 1.02) y la depresión (ECAs: g = 0.72; Estudios no controlados: g = 1.08), que permanecieron estables durante el seguimiento. El análisis preliminar con población de niños y adolescentes mostró tamaños del efecto medios en ansiedad (g = 0.45) y depresión (g = 0.50). No encontramos diferencias significativas entre la TCC-T y la TCC para trastornos específicos. En general, los resultados apoyan la eficacia de la TCC-T para los trastornos emocionales.